Idiopathic eruptive macular pigmentation - uncommon presentation of an uncommon condition - Resham Jayvant Vasani (Wolters Kluwer Medknow Publications, 2018)
Idiopathic eruptive macular pigmentation (IEMP) is an asymptomatic condition with dark brown, nonconfluent lesions chiefly occurring in children and adolescents. The usual sites involved are face, trunk, extremities, and the lesions resolve over few months to years. We report an unusual presentation of this uncommon condition. A 22-year-old male presented with multiple dark-colored asymptomatic lesions on the scalp and forehead for the past 3 years. There was no history of preceding symptoms, drug, or applications, past or family history of such lesions. Examination revealed multiple hyperpigmented macules and barely elevated nonscaly plaques with a velvety feel akin to acanthosis nigricans (AN). Dermoscopy was similar to AN. Blood sugar, thyroid, and lipid profiles were normal. Histology showed "pigmented papillomatosis" concluding the final diagnosis of IEMP. Confluence of lesions is a rarely described phenomenon, with the scalp being a hitherto unreported site. The velvety feel of lesions, the dermoscopic, and histopathological findings further substantiate the hypothesis of this entity being an eruptive variant of AN.